Health Sciences Patrons Use Electronic Books More than Print Books - Miller, Robin Elizabeth (Evidence Based Library and Information Practice, 2017)
A Review of: Li, J. (2016). Is it cost-effective to purchase print books when the equivalent e-book is available? Journal of Hospital Librarianship, 16(1), 40-48. http://dx.doi.org/10.1080/15323269.2016.1118288 Abstract Objective – To compare use of books held simultaneously in print and electronic formats. Design – Case study. Setting – A health sciences library at a public comprehensive university with a medical college in the southern United States. Subjects – Usage data for 60 books held by the library simultaneously in print and electronically. The titles were on standing order in print and considered “core” texts for clinical, instructional, or reference for health sciences faculty, students, and medical residents. Methods – Researchers collected usage data for 60 print titles from the integrated library system and compared the data to COUNTER reports for electronic versions of the same titles, for the period spanning 2010-2014. Main Results – Overall, the 60 e-book titles were used more than the print versions, with the electronic versions used a total of 370,695 times while the print versions were used 93 times during the time period being examined. Conclusion – The use of electronic books outnumbers the use of print books of the same title.